Из истории формализации семантики (Filološke studije, 2019)
The problem of formalizing semantics is connected with the idea of creating a so-called philosophical language. The first step was made by Roger Bacon, the further steps were realized by Francis Bacon, John Locke, Thomas Hobbes, Rene Descartes, Gottfried Wilhelm Leibniz, while the two fundamental ideas – symbolization and combinations of the symbols – were first expressed by Raymundus Lullius. Nicolaus Cusanus gave the idea of the primary language consisting of elementary terms. Louis Hjelmslev demonstrated the method of finding out the primary semantic elements. But it was Isaac Newton who realized the practical approach presenting a fragment of a language in which the forms of words corresponded to their meanings.